The effectiveness of catharsis-education-action (CEA) counseling versus the standard clinic advice for the management of type 2 diabetes mellitus at out-patient family medicine clinic a randomized controlled trial - Limoso, David Dexter V.
Background: The burden of suffering of diabetes is immense. The Family Medicine clinic averages more than 200 cases of diabetes per month, about 6.7% of the total cases seen, and ranking consistently in the top ten morbidities. Many studies have concluded that counseling is effective as an intervention in better management of patients with diabetes resulting to improved quality of life. The Catharsis-Education-Action (CEA) counseling is a 15-30 minute method of counseling that uses the biopsychosocial approach, addressing not just the physical illness but also the emotional impact of that illness. The counseling intervention consists of the following steps: (1) Catharsis elicits emotions and perceptions of patient about his illness and identifies the emotionally critical misperceptions (ECMs); (2) Education corrects the misperceptions; (3) Action consists of recommendations and prescriptions offered by the doctor.This study investigates the effectiveness of CEA counseling specific for the management of diabetes in improving the quality of life of patients.
Objectives: To determine the effectiveness of Catharsis-Education-Action (CEA) counseling versus the standard clinic advice on improvement of quality of life score in management of type 2 diabetes in a randomized controlled trial. Research Design & Methods: A total of 166 patients diagnosed with type 2 Diabetes mellitus were randomized to either CEA counseling group or the standard clinic advice group. Patients were asked to complete the quality of life questionnaire, Audit of Diabetes-Dependent Quality of Life (ADDQoL), at baseline and after intervention. The score of the different items of quality of life score were statistically analyzed and compared within and between the two groups of intervention. Metabolic outcomes which included FBS and HbA1c were also measured at baseline and after intervention. Similarly, values of FBS and HbA1c were statistically analyzed and compared within and between the two groups of intervention. Results: Using paired student t-test, the quality of life scores and mean difference increased from baseline to after intervention in both standard clinic advice group and CEA counseling group, with statistically significant difference (p value < 0.05). In repeated measures ANOVA, the within-subject effects analysis showed that both standard clinic advise and CEA counseling is effective in improving quality of life scores from baseline and after intervention with statistically significant difference (p value > 0.05).
Independent student t-test analysis showed that there is an increased mean difference on quality of life scores after intervention between CEA counseling and standard clinic advise. CEA counseling produces statistically significant improvement in quality of life scores than standard clinic advise (p value < 0.05). Repeated measures ANOVA revealed that in between-subject effects CEA counseling has greater effect in improving quality of life scores compared to standard clinic advise with statistically significance difference (p value > 0.05). Mean difference increased with improvement in FBS and HbA1c values from baseline to after intervention in both standard clinic advice group and CEA counseling group, with statistically significant difference (paired student t-test; p value < 0.05). However, mean difference and decrease in FBS and HbA1c after intervention is comparable between the two groups (independent student t-test; p value > 0.05). Repeated measures ANOVA within-subject effects showed statistically significant difference in improvement of FBS AND HbA1c in both groups. However, in between-subject effects, CEA counseling has greater effect in improving FBS and HbA1c values compared with standard clinic advice. Conclusion: The Catharsis-Education-Action (CEA) counseling and standard clinic advise significantly improved the quality of life scores among type 2 diabetes mellitus patients. However, the improvement in quality of life score was significantly better in diabetic patients given the CEA counseling than those given the standard clinic advise.
Thesis (MS Clinical Medicine)--University of the Philippines Manila
Keywords: Diabetes mellitus, non-insulin-dependent.